Analisis Rancangan Lereng Disposal Area Pit D Pada PT. Aman Toebilah Putra Kabupaten Lahat Provinsi Sumatera Selatan - Al Anhar Hardianto; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. PT. Aman Toebilah Putra is one of the coal mining companies located in Lahat Regency, South Sumatera. At this time PT. Aman Toebilah Putra  is exploiting coal, and is doing mine out in mining area especially at Pit A location, and Pit C. The location to be used as overburden material shelter is Pit D, which will be examined the geometry design of the disposal slope.Slope stability analysis with Slide v.6.0 software and use janbu and bishop method (limit equilibrium) and Hoek and Bray Method. with geometric measurement data of the disposal slope in the field as well as laboratory test parameters namely weight of content, cohesion and internal shear angle. In addition, an evaluation was performed for the redesign of the geometry of the disposal slope and the design of the overburden material addition of the geometry of the disposal slope to obtain the value of the safety factor > 1,25 or in a safe and stable condition. Characteristics of lithologic mechanics in the disposal area of Pit D based on laboratory data obtained are known to have a weight value of 25.08 kN/m3 of soil content, cohesion: 15.9 kPa, and shear angle in 19,27°, so the design of the disposal area less safe and stable because the value of FK is less than <1,25. After the evaluation of the geometry of the disposal slope, the final disposal geometry design value is obtained: on the elevator 1 single slope 35°, 5 meters high, 6 meters wide bench.Keywords : Slope, geometry disposal, janbu and bishop method, Mining Software, Hoek and Bray Method.